Empowering College Girls: From Research Insights to AI-Based Solutions for Menstrual Health and Academic Success - Soni, Monali Saurabh; Agrawal, Khushi; Parikh, Prakruti; Bharadva, Payal; Myangar, Mansi (Journal of Neonatal Surgery, 2025)
Menstrual health plays a crucial role in the academic performance and overall well-being of female college students, yet it remains insufficiently addressed within institutional frameworks. This study investigated the challenges associated with menstruation, including physical discomfort, psychological stress, stigma, and reduced academic engagement. A cross-sectional survey of 255 female students (aged 17–22 years) from paramedical and non-medical disciplines was conducted using a structured, expert-validated 44-item questionnaire. Statistical analysis (SPSS v28) revealed significant differences in awareness of premenstrual syndrome (p = 0.031) and the role of exercise in symptom management (p = 0.008). Menstrual cramps, bloating, mood swings, and anxiety were the most reported symptoms, with passive coping strategies preferred over exercise (<14%). An educational intervention integrating exercise guidance and artificial intelligence (AI)-driven menstrual health applications demonstrated an 82% improvement in awareness and motivated 61% of participants to consider adopting healthier lifestyle practices. These findings underscore the potential of AI-enabled digital health platforms, when combined with targeted educational strategies, to enhance menstrual health literacy, reduce stigma, and support academic productivity. Future research should explore the long-term effectiveness and scalability of such AI-based interventions within higher education institutions.